Positive and less positive outcomes of corporate culture - Alvesson, Mats, 1956- (SAGE knowledge. Cases., 2016)
This case presents a field study of a Swedish computer consultancy company (CCC), in terms of the organizational structure and culture of the firm, social relations with other companies, and innovative ideas that led to its growth. The case study also illustrates the complexities of performance management and the potential significance of cultural meanings and values for corporate results.